Relation between attitudes towards the indebtedness and self-discrepancy in chilean pedagogy students - Denegri Coria, Marianela (2017)
Globalization has affected different social norms and dynamics, emphasizing practices associated with consumption and indebtedness. In this context, Pedagogy undergraduate students are a group of interest due to the fact that they are active citizens and, at the same time, they will be responsible of educating a new generation of citizens. Therefore, the present study aimed to identify the association between demographic, self-discrepancy and psychological variables and the attitude toward indebtedness of undergraduate students of Pedagogy in Mathematics, Spanish and History from the North, Center and South zones of Chile. The sample was composed of 1085 Pedagogy undergraduate students of both genders enrolled in universities belonging to The Chilean Universities Rectors Council. The study used a quantitative design with a descriptive-correlational scope. Participants responded the Scale of Attitudes toward Indebtedness and the Self-Discrepancy Scale. The results showed a positive association between different dimensions of self-discrepancy and hedonist attitude toward indebtedness. Austere attitude toward indebtedness showed a negative association with social self-discrepancy. About gender different, results showed that women reported more austere attitudes. The importance of studying this phenomenon related to the necessity of preventing indebtedness and promoting useful strategies to acquire products and services, considering the regulations and dynamics of postmodern societies.